Evaluating the Fairness of Police Discretion in the Resolution of Traffic Cases - Syahtama, Dany; Putri, Hanuring Ayu Ardhani; Aini, Firstnandiar Glica (Jurnal Ilmu Hukum Kyadiren, 2026)
The discretionary authority of the Indonesian National Police (Polri) serves as a critical instrument in handling traffic-related criminal cases. Nevertheless, its implementation frequently raises debates concerning legal boundaries, accountability, and the consistency of field practices. This study aims to analyze the legal foundations and normative regulations governing police discretion and to examine the forms and mechanisms of its implementation at the Sragen Police Resort. Employing an empirical juridical method supplemented with normative analysis and in-depth interviews with investigators, the study finds that police discretion rests on a strong legal framework, including Law No. 2 of 2002, the Criminal Procedure Code (KUHAP), and the Law on Road Traffic and Transportation (UULAJ). However, its practical application is significantly shaped by legal considerations, social context, and the judgment of individual investigators. A Restorative Justice approach emerges as the dominant model in resolving traffic cases. The study concludes that discretion functions effectively as a tool for achieving substantive justice, although more standardized technical guidelines are required to ensure greater uniformity and accountability in law enforcement practices.